Volume 3: 19th International Conference on Advanced Vehicle Technologies; 14th International Conference on Design Education; 10 2017
DOI: 10.1115/detc2017-68197
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of the Effects of Design Project Length on Team Collaboration and Leadership in Senior Mechanical Engineering Projects

Abstract: This paper describes exploratory research regarding leadership and communication within undergraduate engineering design teams. The case study was performed on student design projects of one and two semester duration to begin to assess the impact of project length on leadership and communication within the design teams. Data was collected using a survey that was given to the participants in three capstone design projects in Clemson University’s senior design course. The survey was administered within one month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Some EL educators made the case for EL curriculum to be embedded into capstone courses where evaluation and assessment could occur through project implementation (Novoselich & Knight, 2018). Efforts to assess leadership development in capstone courses related to leadership effectiveness within teams (Novoselich & Knight, 2018), the impact of the project timespan on leadership development (Righter et al., 2017), and leadership behaviours appropriate for capstone situations compared to workplace needs (Chowdhury et al., 2020). While many of these studies report success in leadership development embedded into coursework, they also provide important critiques for the model.…”
Section: Engineering Leadership Researchmentioning
confidence: 99%
“…Some EL educators made the case for EL curriculum to be embedded into capstone courses where evaluation and assessment could occur through project implementation (Novoselich & Knight, 2018). Efforts to assess leadership development in capstone courses related to leadership effectiveness within teams (Novoselich & Knight, 2018), the impact of the project timespan on leadership development (Righter et al., 2017), and leadership behaviours appropriate for capstone situations compared to workplace needs (Chowdhury et al., 2020). While many of these studies report success in leadership development embedded into coursework, they also provide important critiques for the model.…”
Section: Engineering Leadership Researchmentioning
confidence: 99%
“…The instrument has been further refined to investigate leadership structure and communication in design teams [72]. The modified survey instrument was used to establish the leadership structures and communication patterns in selected Capstone design teams.…”
Section: Engineering Leadership Studiesmentioning
confidence: 99%
“…The study explored the impact of the project's length on the establishment of formal leadership roles and the differences in frequency and duration of communication. The study identified that the two-semester teams appeared to function as a multiteam system (MTS) or a system of teams [72].…”
Section: Engineering Leadership Studiesmentioning
confidence: 99%
“…The case study was selected as a research method because it allows the study of the team in its natural environment thus enabling the researcher to identify challenges and trends within this natural context [48]- [50]. A previous study undertaken to explore the impact of project length on leadership structure, however, suggested that the leadership structures were more complex than could be determined with the selected approach [51]. A single two-semester design team with ten members was selected to explore these complex leadership structures with the study leader serving as a graduate student advisor on the team with a faculty coach.…”
Section: Leadership and Communication Case Studymentioning
confidence: 99%